2000
DOI: 10.1088/0022-3727/33/14/307
|View full text |Cite
|
Sign up to set email alerts
|

Stability analysis of thin viscoelastic liquid film flowing down on a vertical wall

Abstract: This paper investigates the stability of thin viscoelastic liquid film flowing down on a vertical wall using a long-wave perturbation method to find the solution for generalized nonlinear kinematic equations with a free film interface. To begin with, a normal mode approach is employed to obtain the linear stability solution for the film flow. The linear growth rate of the amplitudes, the wave speeds and the threshold conditions are obtained subsequently as the by-products of linear solutions. The results of li… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
26
2

Year Published

2001
2001
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 39 publications
(31 citation statements)
references
References 21 publications
3
26
2
Order By: Relevance
“…This phenomenon agrees well with the conclusion given by Bird et al 18 By setting nϭ1, the results of a classical Newtonian flow are obtained. As compared to the modeling results given by Cheng et al, 17 it is found that both solutions agree well with each other. …”
Section: B Nonlinear Stability Solutionssupporting
confidence: 75%
See 1 more Smart Citation
“…This phenomenon agrees well with the conclusion given by Bird et al 18 By setting nϭ1, the results of a classical Newtonian flow are obtained. As compared to the modeling results given by Cheng et al, 17 it is found that both solutions agree well with each other. …”
Section: B Nonlinear Stability Solutionssupporting
confidence: 75%
“…After deriving the viscoelastic analog of the Orr-Sommerfeld equation with the requisite boundary condition, Gupta pointed out the viscoelastic effect can destabilize the film flow. Cheng et al 17 further studied the nonlinear stability analysis of thin viscoelastic liquid film flowing down on a vertical wall. They also demonstrated that the viscoelastic property has a destabilizing effect on the nonlinear film flow system.…”
Section: Introductionmentioning
confidence: 99%
“…The higher-order terms of OðE 2 Þ can be neglected since they are of little influence on the system [18,19]. The set of zeroth and first order equations can now be expressed as follows: Oð1Þ :…”
Section: Long Wave Analysismentioning
confidence: 99%
“…It is worth mentioning here that the investigations on the flow and stability characteristics of non-Newtonian fluids [16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32] have shown that the deviation from Newtonian rheology has a significant influence on the stability characteristics of non-Newtonian films. The above investigations have analyzed the flow characteristics and the associated time dependent properties and have developed suitable conditions for homogeneous film growth that would be relevant for industrial applications.…”
Section: Introductionmentioning
confidence: 99%